VD_FINDINFO Jug / 2015 / 462 vom 5. März 2015 - VD Tribunal cantonal (2015)
PLAIGNANT, FRAIS DE LA PROCÉDURE, INDEMNITÉEN GÉNÉRAL, ADMISSION DE LA DEMANDE | 398 al. 1 CPP (CH), 406 al. 1 let. d CPP (CH), 427 al. 2 CPP (CH), 432 CPP (CH)